Model Sistem Pengajuan Judul Skripsi Berbasis Website Menggunakan UML - Sitorus, Rina Afriani (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
To obtain a bachelor's degree at a university, students must complete a skripsi (undergraduate thesis). In completing a skripsi, there are many things that must be overcome, such as preparing and submitting the skripsi title to the Head of the Study Program. To provide time efficiency for students, it is necessary to develop an easy-to-use application for submitting a skripsi title online. This research uses a qualitative approach method that focuses on observation.  The model of the system is based on the SDLC Waterfall method which has a structured flow. This designed system model will assist in designing a website-based skripsi title submission system which will help students and lecturers to carry out the process of submitting skripsi titles to the Head of the Study Program for an official decree containing the name of the skripsi supervisors and the acceptance of skripsi title.